Lactic acid bacteria isolated from sremska sausage using molecular methods. (September 2019) - Borovic, B; Velebit, B; Veskovic, S; Baltic, T; Milijasevic, M; Jankovic, V; Vranic, D
Abstract: Sremska sausage is a traditionally fermented dry sausage, which is produced in northern Serbia (Vojvodina). It is made from pork with the addition of back fat and natural spices. The entire manufacturing process lasts for 21 days. The goal of this study was to create a collection of lactic acid bacteria isolated during sausage fermentation and identify them using molecular methods. A total of 50 isolates from different stages of fermentation were identified by molecular methods. Ln. mesenteroides, Pediococcus pentosaceus and Lb. sakei are the predominant microorganisms in the sremska sausage studied.